Therapeutic Communications Phase In Children Down Syndrom: Case Study In Bantul, Yogyakarta - Suciati Bahar Sarro, Adhea Rifty (Program Studi Ilmu Komunikasi FISIP UM Buton, 2020)
Therapeutic communication is an attempt at healing through communication. In the case of Down Syndrome child therapy, therapists are required to pay attention to factors that influence the implementation of therapy so that communication is carried out effectively so that healing goals can be achieved. This study intends to describe the therapeutic communication phase of therapists with children with Down syndrome in forming independence in SLBN 1 Bantul, Yogyakarta. This study uses a qualitative descriptive type with 2 (two) pairs of informants, PT and LN . Data obtained through interviews, observations, and documentation. Based on the results of the study, it can be concluded that there are four therapeutic communication phases which include the pre-interaction phase, the orientation phase, the work phase, and the termination phase. In the work phase, the therapist uses YouTube in play therapy. The use of this new media has been proven to improve children's moods and thus speed healing. The four phases of therapeutic communication have been carried out effectively by a therapist informant and it is proven that children with down syndrome can experience changes toward healing in increasing independence, interacting, and building caring attitudes. The other informants did not carry out the four phases of therapeutic communication to the maximum, causing children to be lazy to attend school and slow to develop towards a better direction. Keywords: therapeutic communication, pre-interaction phase, orientation phase, work phase, termination phase